Design and Implementation of Smart Forklift for Automatic Guided Vehicle Using Raspberry Pi 4 - Florentinus Budi Setiawan; Phoa Marcellino Siva; Leonardus Heru Pratomo; Slamet Riyadi (Universitas Muhammadiyah Yogyakarta, 2021)
Automatic Guided Vehicle (AGV) pallet truck is widely used in the industry. This kind of AGV is such a combination of the ordinary AGV used forklift mechanism. The forklift mechanism is employed for lifted up or carrying things from one place to another place. As the technology has been developed along with the industry revolution 4.0, therefore, the activity could be done automatically by using a robot-like AGV pallet truck. Basically, the working principle of the AGV pallet truck is similar to the ordinary forklift whereas the AGV pallet truck is automatically operated. DC motor is applied as the driving force for the uplifting and down lifting process in the forklift mechanism of the AGV pallet truck. DC motor is chosen because it has large torque which is advantageous for lifting loads. Unfortunately, DC motor also owns some disadvantages such as high maintenance fees and less precision. This study proposes a smart forklift mechanism for AGV pallet trucks that utilizes a stepper motor and ultrasonic distance sensor. This smart forklift mechanism is equipped with raspberry pi model B as the main microcontroller and combined with an ultrasonic distance sensor. The result of the ultrasonic distance sensor has an error approaching zero percent so the precision of the height can be fully controlled. Step / Revolution (SPR) method makes the stepper motor can move smoothly like micro-step and also the number of rotations can be controlled as we want.